Partial Cryptography in Digital Media Environment Based on ECC Algebra - Abdul Wahab, Hala; Sameer, Rafal (Iraqi Journal of Science, 2024)
In recent years, Elliptic Curve Cryptography (ECC) has attracted the attention ofresearchers and product developers due to its robust mathematical structure andhighest security compared to other existing algorithms like RSA. It is found to givean increased security compared to RSA for the same key-size or same security asRSA with less key size. In this paper a new approach is proposed for encryptingdigital image using the arithmetic of elliptic curve algebra. The proposed approachproduced a new mask for encrypt the digital image by use a new convolutionprocesses based on ECC algebra operations and work as symmetric cryptographicsystem instead of asymmetric system. A new approach combined both compressionand encryption algorithms, the compression algorithm used here is discrete wavelettransform to decompose the image information into four subbands (LL, LH, HL, andHH), then LL subband will be encrypted. The new approach test by executeencryption and decryption processes was more flexible and efficient.